Survey of food consumption patterns of low-income urban groups - Macapil, Maribeth J.; Galvez, Flor Crisanta F. (1997)
A survey was conducted among urban, poor families in Libis, Barangay UP Diliman, Quezon City to determine their attitudes, behaviors, concerns, consumption patterns, and beliefs regarding the food they eat. All household in the area were included in the study. The questionnaire used was designed to be administered in a one-on-one interview. Upon completion of interviews, data from the questionnaires were coded and analyzed. Percentage frequencies and means were obtained on responses from participants. A total of 188 households were included in the master list of the community. Only 139 households participated in the interview. The community is made up of relatively young citizens. Sixty-six percent of the respondents and 53% of the husbands were below 40 years of age. Sixty-eight percent of the children were below 12 years of age. Ninety-three percent of the families have at least one person working or earning a living. Among the most common jobs that the residents have are in the categories of driver, construction worker, security guard, domestic helper/laundry woman, carpenter, sales representative, etc. Ninety-two percent of the household of monthly incomes less than P10,000.00. All the families spent P5,000.00 or less for food. The wife is the one who most often obtains the food for the family. Ninety-five percent of the households but their food from street peddlers (11.5%), sari-sari stores (20.1%), talipapa (28.8%), market (57.6%) and grocery stores (8.6%). Most of the families buy food everyday (36.0%) or once a week (33.1%). They buy meat, fish, milk, eggs, fruits and vegetables at least twice a month. Mungbean (whether as beans or as sprouts) is the most frequently bought legume with 83.4% of the families buying the beans at least twice a month and 43.2% buying the sprouts (togue). Two families (1.4%) at Libis inidicated that they eat less than three times, 22.3% eat three times, and 76.3% eat more than three times a day.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Food consumption -- Philippines; Family -- Philippines -- Food consumption